If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7(-1x + 21) = 42 Reorder the terms: -7(21 + -1x) = 42 (21 * -7 + -1x * -7) = 42 (-147 + 7x) = 42 Solving -147 + 7x = 42 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '147' to each side of the equation. -147 + 147 + 7x = 42 + 147 Combine like terms: -147 + 147 = 0 0 + 7x = 42 + 147 7x = 42 + 147 Combine like terms: 42 + 147 = 189 7x = 189 Divide each side by '7'. x = 27 Simplifying x = 27
| 2+-s=5 | | x^3-3x+0.25=0 | | 8b=b+35 | | 2n+3.74=10n-2.25 | | 4.25+3.5+x=11 | | 14+12x=-51+x | | 7(5+t)-4(t+1)= | | 2(3x+4)=6-(2x+5) | | 4.25+3.5x=11 | | 7x-5=50 | | y=sqrt(x) | | 2x-4=3x-26 | | 3+2z=5 | | 175*4=x | | -21+10.4x=12.2x-32.34 | | x+x+10cm=42 | | 5-2f=1 | | x+x+10cm=41 | | -2y^2-5y=-5 | | (y+11)=9 | | 8y+44=0 | | 3*n-13=5 | | 9d+3d-4=5d | | 2x-5(3x-1)=-8 | | -(y-3)=2y+3-3y | | .6x+8=41 | | 9+b=24 | | 9-2*b=1 | | (x-3)(x^2-6x)=7 | | 5x=-3x+35 | | 5(Y+4)=6u | | u-2+-11=-15 |